Evaluation of User Satisfaction on Taxsee Driver Application using User Experience Questionnaire (UEQ) - Rianda, Rahmad Didho; Rahmawita, Medyantiwi; Syaifullah, Syaifullah; Jazman, Muhammad (Sistemasi: Jurnal Sistem Informasi, 2025)
Technological advancements have made daily life more convenient, particularly in the field of online transportation services. To stay competitive in an increasingly tight market, companies like Maxim must continuously innovate to improve service quality. Maxim offers two applications: Maxim for passengers and Taxsee Driver for drivers. The Taxsee Driver app facilitates drivers in finding passengers, managing trips, and streamlining payment processes. However, the app still faces several technical issues, such as bugs during peak hours, fake orders, and GPS inaccuracies, which impact drivers' experiences and earnings. This study aims to evaluate the Taxsee Driver app using the User Experience Questionnaire (UEQ) to identify its strengths and weaknesses from the drivers' perspective. Through this analysis, key aspects such as interface design, responsiveness, security, and navigation integration can be assessed objectively. The evaluation results are expected to provide valuable insights for developers to enhance service quality, improve driver satisfaction and loyalty, and strengthen Maxim's position in the online transportation industry.